Question #299fa

1 Answer
Mar 10, 2017

Answer:

#2(9-x)+(9-x)=9#

Explanation:

We have to write an equation such that

9 equal to some expression. On solving the

equation we get the other number.

The other number is #x#

As per the statment #2xx(9-x)# is the other number

The difference is #9-x#

The value of the other number plus the difference between the two numbers is equal to #9#

Then the equation is -

#2xx(9-x)+(9-x)=9#

Let us verify it -

#18-2x+9-x=9#
#27-3x=9#
#-3x=9-27=-18#
#x=(-18)/(-3)=6#
#x=6#